Challenges and Solutions for Food Waste Management in the Hospitality Industry: Its Impact on Sustainable Tourism - Sesa Mia Audenada; Nining Yuniati; Moch. Nur Syamsu (TourEcon: International Journal of Tourism and Economic Studies, 2025)
Food waste is a global problem today and is closely related to tourism , especially in the hospitality sector . Every day there are 70 million tons of food waste wasted and there are about 1.2 billion people living on empty stomach , this inequality needs to be looked at more deeply so that sustainability can be realized , at the research location there are 18 thousand kilograms of waste generated per day and will be different in number if the high season or holiday season . There are more than 700 sectors in the form of hotels , restaurants and cafe that are economic drivers and emissions​​ contributors . The purpose of this research is to find a solution to the problem gap, namely one side has excess food and one side needs food . The method used in this research is qualitative . The data obtained are primary and secondary data, through observation , interviews , and documentation . The results of this study indicates that the field is considered supportive to conduct a food rescue program following the novelty of the research that researchers offer .